An Industrial systems design study on Juno Cars, Inc. (GM AutoWorld Shaw) - Falcis, Charlene Therese; Lynn, Jaimini Juris; Ricalde, Rebecca; Varona, Andrew James (College of Engineering, 2003)
The local automotive industry appears on its way to recovery from a vehicle sales slump dating from the Asian financial crisis. For General Motors (GM) Automobile Philippines, there was an increase in revenue due to both sales and services. GM Shaw, one of its dealers, ranked as one of its best performers last year. Because of strong performance, the dealership must be prepared to handle more customers without sacrificing efficiency, accuracy, and customer service. A study of the total system of GM Shaw, Inc gave an opportunity to identify and correct both existing and potential problem areas that will hinder the system's ability to perform well in the coming years. The yearly financial reports indicate that GM Shaw is profitable but is very dependent on its current assets. Thus, company should concentrate on increasing profit without holding costly inventories. Taking a look at their monthly financial statements, it can be deduced that GM Shaw can earn more profit from its service operations. The focus of the study is therefore improving service operations. The total system time of vehicle spent in the service area is basically long. This results to a low vehicle turnover. Therefore, the solution lies in reducing the total system time to maximize the company's capacity. The goal of the alternatives generated was to reduce total system time by reducing the total system time elements. It was recommended that W2 double loaded parking layout be applied to the facility to diminish time of movement. Express estimates, early picks, and afternoon drops are among the marketing alternatives that can greatly reduce total time in the system. The alternatives were evaluated using simulation analysis. It allowed the recommendations to be applied in ?real life? system and at the same time check whether it is really beneficial to the company. Environmental issues are also a great concern of any business sectors. That is why GM Shaw should develop an environmental awareness programs to instill care for the environment. This will indirectly contribute to reduced costs and increased savings for the company.